PERAN PERUSAHAAN DALAM MELINDUNGI HAK TENAGA KERJA ASING - Simamora, Priskila Putri; Susanti, Erna; Wardana, Khristyawan Wisnu (Jurnal Ilmiah Advokasi, 2025)
This research is directed at examining 2 (two) problems, namely first, legal protection of the rights of foreign workers based on Samarinda District Court Decision Number 65/Pdt. Sus-PHI/2017/PN. Smr Jo Supreme Court Decision 1121 K/Pdt.Sus-PHI/2018 and secondly, legal liability by companies for the rights of foreign workers who are not stated in the employment agreement. The study of this problem was carried out using doctrinal legal research.The results of this research conclude that firstly, legal protection for the rights of foreign workers has been regulated in Law Number 13 of 2003 concerning Employment as preventive protection and is confirmed in the ruling of the Samarinda District Court which granted some of the claims of foreign workers with consideration of several rights claimed by them. foreign workers are not included in the work agreement as repressive protection, and secondly, legal responsibility by the company for the rights of foreign workers who are not stated in the work agreement, namely fulfilling the company's obligations which is one of the conditions for employing foreign workers in Indonesia. Keywords: Accountability; Protection; Rights